Repair of cleft lip on relatively older children with anthropometrical surgical outcome - Rahman, S; Majumdar, SK; Ahmed, M; Singha, JL; Majid, MA; Hasan, MR (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2006 Jan;15(1):89-95The abstract of this article is available on the PubMed website